2017
DOI: 10.1002/term.2465
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of thermoresponsive, photocrosslinkable hydrogels derived from decellularized tendon and cartilage extracellular matrix for cartilage tissue engineering

Abstract: Tissue engineering using adult mesenchymal stem cells (MSCs), a promising approach for cartilage repair, is highly dependent on the nature of the matrix scaffold. Thermoresponsive, photocrosslinkable hydrogels were fabricated by functionalizing pepsin-soluble decellularized tendon and cartilage extracellular matrices (ECM) with methacrylate groups. Methacrylated gelatin hydrogels served as controls. When seeded with human bone marrow mesenchymal stem cells (MSCs) and cultured in chondrogenic medium, methacryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 34 publications
0
35
0
Order By: Relevance
“…However, contrary studies found that cartilage T-dECMs had a limited or failed capacity to induce chondrogenic differentiation [88,89]. For example, only a small portion of cartilaginous and fibrous tissue was formed when decellularized pig ears seeded with porcine BMSCs without chondrogenic induction were implanted into nude mice.…”
Section: Chondrogenic Differentiationmentioning
confidence: 99%
“…However, contrary studies found that cartilage T-dECMs had a limited or failed capacity to induce chondrogenic differentiation [88,89]. For example, only a small portion of cartilaginous and fibrous tissue was formed when decellularized pig ears seeded with porcine BMSCs without chondrogenic induction were implanted into nude mice.…”
Section: Chondrogenic Differentiationmentioning
confidence: 99%
“…Like solubilized bone dECM, cartilage solubilized dECM can be used to deliver cells, drugs, and other bioactive molecules for cartilage regeneration.The most common limitation of hydrogels formed from solubilized dECM is poor mechanical properties. For this reason, different approaches to enhance the mechanical properties of solubilized dECM have been implemented, including mixing with biological polymers, such as alginate,78,79 and crosslinking using physical, UV photochemical,26,62,82 or chemical83,84 methods. Although such treatments create hydrogels that are physically stable, they can also limit the chondrogenic capacity of the hydrogel.…”
mentioning
confidence: 99%
“…While these studies demonstrated that PLL treatment was well tolerated by cells [55,62,63,67], a critical objective of the current investigation was to verify that lentivirus immobilization did not negatively impact the native structure or composition of CDM, which in turn influence cell attachment and viability. Minimizing alterations to CDM is of the utmost importance as processing techniques including excessive chemical crosslinking [47,68], pepsin digestion [34,69], encapsulation in PLGA microspheres [23,70], incorporation with carbon nanotubes [71], or functionalization with methacrylate groups [17,72] can inhibit cell attachment [47,68,71] and compromise the ability of CDM to support chondrogenesis [47,[68][69][70] or endochondral ossification [17]. In the current study, there was no difference in the baseline biochemical composition between NT and eGFP-transduced constructs (reported in the caption of Fig.…”
Section: Discussionmentioning
confidence: 52%